Preferential factors and usability effects on vehicle modifications for the Malaysian independent disabled driver - Khairul Anwar Mohd Dahuri, Mohd; Nasir Hussain, Mohd; Fasiha Mohd Yusof, Nor; Kasim Abdul Jalil, Mohamad (International Journal of Engineering and Technology, 2018)
The usability of driving modifications for a person with disabilities is known to be an important aspect in addressing the independent vehicleâ€™s driving capabilities. The existence of assistive modifications such as hand control, secondary control, foot control, and also the wheelchair assisted vehicle, which were developed to accommodate limitations were found to be widely used. A survey was conducted on 202 Malaysian independent disabled drivers from Kuala Lumpur, Selangor, Perak, Johor Baharu, Terengganu, and also Melaka. The components evaluated in the survey include the origin of modification used for driving, factors influencing the decision on the type of vehicle modification, usability difficulties when modification is in use, the satisfaction level of product appearance, as well as to understand user preferences when making decisions between modifications. A Likert scale of 1 to 5 was used as measurement, in order to rate the score given by the responses for each question in the survey. As a result, it was discovered that aspects such as the modification colour, shape, the toggle, pedal grip, regulation, modification availability, and movement limitation on the involved body part are among the major factors influencing the driver to make modification for driving purposes. Major factors were also found to influence the driving modification preferences to suit the category of disabilities. It was also discovered that components such as the availability of modification information and emergency driving situations are some of the least important factors influencing the decision to make and select a suitable driving modification. However, these less important components must not be ignored as it also contributes to the improvement for independent disabled driving, and also for the purpose of assistive product development.Â Â